Study of the attitude and participation of the population in the preventive and screening examinations and implementation of these examinations in the health care system - V. F. Levshin; N. I. Slepchenko; N. I. Ryzhova; L. A. Sаvluchinskaya; L. G. Solenova (Лечащий Врач, 2022)
The purpose of this medical and social research is to study the knowledge, attitude and participation of the population in the preventive and screening examinations and to analyze the real practice and results of the programе of preventive examinations. For the period from May 2020 to January 2022, the special survey of 461 adults of Moscow residents aged 18-79 years was conducted. The median sample age was 45 years. The number of women in the study sample was 284 (61.6%), men – 177 (38.4%). The survey using a unified and structured questionnaire was conducted through individual and anonymous interviews. Statistical processing of data was carried out by methods of descriptive statistics and one-factor analysis of variance. 33.2% (95% CI 28.8-37.6) of respondents in the study sample did not know or had misconceptions about the purposes of preventive and screening examinations. The majority, 65.5% (95% CI 61.07- 69.9), had limited or insufficient knowledge, with only 1.3% (95% CI 0.25-2.35) of respondents having relatively sufficient knowledge. 40.6% (95% CI 36.03-45.07) of the respondents knew nothing about the scientifically proven measures and methods for cancer prevention and only 19.1% (95% CI 15.44-22.76) had relatively sufficient knowledge. Less than half of the respondents, 43.8% (95% CI 39.18-48.42). Had sufficient motivation and readiness to undergo preventive examinations. Most of the persons who underwent medical examinations received an incomplete set of studies and measures indicated for preventive examination. Most often, questionnaires, measurement of body mass index, analysis of feces for occult blood, examination for the detection of visual and other localizations of oncological diseases and individual preventive counseling are not performed. The majority of respondents either never underwent the preventive examination or received an incomplete set of studies and measures indicated for preventive medical examination. Such inadequate implementation of the preventive survey program for population has a small effect, or even the absence of it. The main reasons for the ineffective introduction of preventive examination are named and approaches to the development and improvement of the preventive examination program. in the health care system are proposed.